Contesting the hydrocarbon frontiers: state depoliticizing practices and local responses in Peru - Schilling-Vacaflor, Almut; Flemmer, Riccarda; Hujber, Anna (2018)
Abstract: Based on primary sources, this article analyzes 150 participatory events related to planned hydrocarbon projects in Peru (2007-2012). Therein, it sheds light on state depoliticizing practices and local populations' contestations thereof. We argue that participation in the extraction sector has not enabled effective participation and has instead been used to pave the way for expanding the extractive frontiers. We find that the state entity responsible for carrying out the events applied three main depoliticizing practices: (a) the organization of exclusionary participatory processes, (b) the provision of pro-extraction information, and (c) the identification of critical actors and discourses in order to formulate recommendations on how to weaken resistance against the planned activities. This study also reveals that local populations often contested the participatory events and identifies subnational patterns of local contestation. We find that higher degrees of contestation were fu